The effect of pre-event sport massage on jumping performance among Negeri Sembilan cycling team / Muhammad Sany Kasbolah - Kasbolah, Muhammad Sany (2014)
Purpose: To investigate whether there are differences in pre-event sport massage on jumping performance among Negeri Sembilan cycling team. Method: 36 subjects which consist of high performance cyclist which also from Negeri Sembilan Cyclist Association. They need to do jumping test which is vertical jump test. The result of the data then had been analysed. Result: In the testing of vertical jump test, the mean of control group is 1.36±1.20. The significant is 0.00. In the test of experimental group, the mean for vertical jump test is 3.06±2.41. The significant is 0.00. Which mean there is a different in agility performance between single and double based on comparing mean. Based on the descriptive statistic, experimental have better jumping height in test than control group. Conclusion: There is a significant different in jumping performance between control and experimental group. Despite the experimental group have better jump height than control group, the different is not great. This show that the even the pre-event massage is used every team in cyclist, but from the jumping performance is almost the same for both group.